Narasi Nilai Kepemimpinan Astha Brata Dalam Manajemen Kepemimpinan Kepala Sekolah Pada Sekolah Pinggiran - Angga Prasetiya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The term suburban school emerged as a result of the polarization between schools located in cities and suburban areas. Negative stigma is often attached to suburban schools, with all their limitations.Therefore, the skills of the principal as a leader are highly demanded in school administration in order to create a golden generation in 2045. The eight values of Astha Brata's leadership are ideal values that must be possessed by a leader. The actualization of Astha Brata's leadership values by the principal in suburban schools is absolutely necessary, because of the peculiarities of the problem. This study describes the form of actualization of Astha Brata's values on the leadership management of the principal at a suburban school in Central Aceh. Data collection techniques come from written sources such as books, as well as scientific articles, as well as photos from documentation of school activities. The form of actualization is analyzed based on the problem and the solution to the problem is proven by school documentation in the form of photographs, so that an overview of the actualization of the value of Astha Brata's leadership in the leadership management of school principals in suburban schools can be comprehensively summarized.